Peran Komunitas Pencinta Alam Dalam Pariwisata Berbasis Masyarakat Di Desa Wisata Kedung Gede, Lenteng Agung - Gagih Pradini; Anisa Putri Kusumaningrum; Heliyu Binti; Putri Aulia Ardani; Bambang Subiyanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
Community-based tourism has become an increasingly popular approach in developing tourist destinations in various regions. Kedung Gede Tourism Village has interesting natural potential and unique local culture which can be used as a main attraction for tourists. However, the presence of tourists will pose new challenges to natural and cultural preservation. So there is a need for involvement from local communities, such as the nature-loving community, in maintaining a balance between tourism development and environmental and cultural preservation in developing destinations in this tourist village. In this research, it was found that nature-loving communities act as facilitators in connecting tourists with nature and local culture. They also contribute to environmental conservation through reforestation programs and environmental awareness campaigns. Active community participation in managing tourism destinations has increased thanks to the involvement of this community.